Internal left cartoid agenesis: case report and literature review - Vidaurri, Karla P.; Bojórquez, Kimberly O.; Trujillo, Erick G.; Serrano O., Ricardo; Fierro, Armando Ibarra; Arvizu, José A. (International Journal of Research in Medical Sciences, 2024)
Internal carotid agenesis (ICA) is an exceptionally rare condition. It is typically discovered incidentally, often during evaluations for other conditions, and generally asymptomatic due to compensatory collateral circulation. In this case A 57-year-old female with chronic background of anxiety disorder and auricular tachycardia; congenital malformations: imperforate anus with multiple surgical interventions until the age of 15 years old; right ovary agenesis and right kidney hypoplasia.